Importance of Mammography in Breast Cancer Diagnosis in Poland - Dusińska, Aleksandra; Kulej, Piotr; Woźniak, Justyna; Kmieć, Justyna Weronika; Chernysh, Anna-Mariia; Biesiada, Wiktor; Waszczyński, Jakub; Fuczyło, Kamila; Stankevič, Karolina (Quality in Sport, 2025)
Introduction: Breast cancer is the most frequently diagnosed malignancy in women, being the leading cause of death in this group. In Poland, despite an increase in the incidence, there is an insufficient level of participation in screening. Objective: To analyse the role of mammography in breast cancer diagnosis and assess its impact on mortality and early detection of cancerous lesions in Poland. Methodology: Statistical data from Polish and international databases, such as the National Cancer Registry and GLOBOCAN, and scientific literature available on online platforms were analysed. Results: Mammography significantly contributes to the early detection of breast cancer, which improves prognosis. In Poland, the percentage of women participating in screening programmes is 27%, one of the lowest in Europe. Planned changes from 2025 may increase the effectiveness of prevention. Conclusions: It is necessary to increase public awareness, intensify prevention campaigns and develop modern diagnostic and therapeutic methods in order to reduce mortality and improve the quality of life of patients.